2021
DOI: 10.1038/s41598-021-88017-w
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic delivery of targeted nanotherapeutic reverses angiotensin II-induced abdominal aortic aneurysms in mice

Abstract: Abdominal aortic aneurysm (AAA) disease causes dilation of the aorta, leading to aortic rupture and death if not treated early. It is the 14th leading cause of death in the U.S. and 10th leading cause of death in men over age 55, affecting thousands of patients. Despite the prevalence of AAA, no safe and efficient pharmacotherapies exist for patients. The deterioration of the elastic lamina in the aneurysmal wall is a consistent feature of AAAs, making it an ideal target for delivering drugs to the AAA site. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Moreover, in LPS-stimulated RAW 264.7 cells, PGG dramatically reduced secretions of TNF-α, IL-1, IL-6, and NO ( Zhang et al, 2021 ). Furthermore, in accordance with the present study, in vivo studies on the animal model of aortic aneurysm showed that PGG nanoparticles suppressed inflammatory cell infiltration and systemic inflammation ( Wang et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…Moreover, in LPS-stimulated RAW 264.7 cells, PGG dramatically reduced secretions of TNF-α, IL-1, IL-6, and NO ( Zhang et al, 2021 ). Furthermore, in accordance with the present study, in vivo studies on the animal model of aortic aneurysm showed that PGG nanoparticles suppressed inflammatory cell infiltration and systemic inflammation ( Wang et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…ROS generated in gastric tissues by activated neutrophils was associated with delayed stomach ulcer healing [ 53 ]. Intracellular antioxidants such as catalase and GSH could neutralize the generated ROS [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“… 62 Systemic delivery of nanoparticle‐conjugated antielastin antibodies also suppressed angiotensin II‐induced AAA progression. 63 These complementary results lend further support to the concept of enhanced ECM proteolytic resistance as a viable AAA suppression strategy.…”
Section: Discussionmentioning
confidence: 66%